Biomass for water defluoridation and current understanding on biosorption mechanisms: A review. Issue 5 (19th January 2018) - Manna, Suvendu; Roy, Debasis; Adhikari, Basudam; Thomas, Sabu; Das, Papita
Abstract : Excessive fluoride (above 1.5 mg/L) containing water consumption for prolonged periods could pose health hazards, for example, dental fluorosis. Longer exposure could also cause skeletal fluorosis leading to the permanent deformity to skeleton. In the current context, use of biomasses for defluoridation would be a most economic and sustainable option for water defluoridation over the available alternatives. This article presents a brief summary of processes used biomasses for fluoride removal from aqueous solutions. This article also discusses the theoretical and instrumental approaches used by the researchers till date to understand the defluoridation mechanisms. The literature survey pointed that theoretical models such as Langmuir and Freundlich isotherms, pseudo‐first‐order and second‐order kinetic models, and different thermodynamic equations were also used to define the defluoridation by biomasses. Apart from the theoretical modeling, several researchers have also tried to understand the biomass‐based defluoridation by applying advanced instruments, for example, FTIR, XPS, NMR, TG, FESEM, and Raman spectroscopic analysis. © 2018 American Institute of Chemical Engineers Environ Prog, 37: 1560–1572, 2018